Formulation and evaluation of skin cleansing gel containing Aloe vera gel - Nguyen , Tiến Thêm; Tran, Thị Huyên; Huynh, Lời (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
The beneficial effects of Aloe vera have been reported, including wound and burn healing, immunomodulatory, anticancer, hypoglycemic, gastro-protective, anti-inflammatory and antifungal, properties. Aloe vera contains anthraquinones, saccharides, vitamins, amino acids; enzymes; inorganic compounds, and miscellaneous. The purpose of this study is to formulate the skin cleansing gel from Aloe vera. The results showed that formulation containing 90.09% (w/w) distilled water, 1.50% carbomer, 0.03% EDTA, 0.30% sodium benzoate, 1,00% Aloe vera gel, 1.50% sand, 0.10% allantoin, 1,00% niacinamide; 3,00% glycerin; 0.70% optiphen (phenoxyethanol, caprylyl glycol), 0.01% Citrus maxima oil, 0.10% PEG – 40, and 0.69% triethanolamin. The prepared gel was evaluated including loss on drying, organoleptic test, pH, viscosity, clean power test.